Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphar.2019.01428
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Activation Is Involved in Acidic Fibroblast Growth Factor Ameliorating Parkinson’s Disease via Regulating Tribbles Homologue 3

Abstract: Parkinson’s disease (PD) is a degenerative disorder of the central nervous system, resulting in loss of dopamine neurons. Excessive endoplasmic reticulum (ER) stress and autophagy dysfunction play a crucial role on Parkinson’s disease (PD) development. It has been showed that acidic fibroblast growth factor (aFGF) alleviates the development of PD by inhibiting ER stress. But the role of autophagy and its relationship with ER stress during aFGF treatment for PD has not been elucidated. We found that both aFGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It has been found that aFGF can play its neuroprotective role in PD by inhibiting ER stress and down-regulating apoptosis-promoting protein TRB3, thus activating autophagy and reducing α-synuclein accumulation ( Zhong et al, 2019 ). TRB3 is mainly induced by the ATF4-CHOP pathway, and it is related to apoptosis induced by endoplasmic reticulum stress ( Ohoka et al, 2005 ).…”
Section: The Role Of Fibroblast Growth Factor In the Pathogenesis Of Parkinson’s Diseasementioning
confidence: 99%
“…It has been found that aFGF can play its neuroprotective role in PD by inhibiting ER stress and down-regulating apoptosis-promoting protein TRB3, thus activating autophagy and reducing α-synuclein accumulation ( Zhong et al, 2019 ). TRB3 is mainly induced by the ATF4-CHOP pathway, and it is related to apoptosis induced by endoplasmic reticulum stress ( Ohoka et al, 2005 ).…”
Section: The Role Of Fibroblast Growth Factor In the Pathogenesis Of Parkinson’s Diseasementioning
confidence: 99%